2013
DOI: 10.1021/cb300396j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Acid-Activated Fluorophores Reveal a Dynamic Wave of Protons in the Intestine of Caenorhabditis elegans

Abstract: Unlike the digestive systems of vertebrate animals, the lumen of the alimentary canal of C. elegans is unsegmented and weakly acidic (pH ~ 4.4), with ultradian fluctuations to pH > 6 every 45 to 50 seconds. To probe the dynamics of this acidity, we synthesized novel acid-activated fluorophores termed Kansas Reds. These dicationic derivatives of rhodamine B become concentrated in the lumen of the intestine of living C. elegans and exhibit tunable pKa values (2.3–5.4), controlled by the extent of fluorination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…in the detection of nerve agents, 15 phosgene, 16 and biologically relevant aldehydes. 17 Furthermore, our work on the AMR scaffold, and more recently the work of Peterson et al ., 18 has shown that the pH range in which these probes respond can be tuned by introducing different functional groups to change the basicity of the amine moiety. We are interested in exploring functionalities that can be used to tune the pH dependent properties of the AMR scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…in the detection of nerve agents, 15 phosgene, 16 and biologically relevant aldehydes. 17 Furthermore, our work on the AMR scaffold, and more recently the work of Peterson et al ., 18 has shown that the pH range in which these probes respond can be tuned by introducing different functional groups to change the basicity of the amine moiety. We are interested in exploring functionalities that can be used to tune the pH dependent properties of the AMR scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we developed a pH-responsive dye, KR35, and used it to monitor pH changes in the intestine of C. elegans [18]. KR35 is activated by acid in a range that is physiologically relevant to the C. elegans intestine, which maintains a pH gradient from anterior to posterior of ~5.5-3.5 [19].…”
Section: Pbo-1 Mutants Have An Abrogated Ph Wave In the Intestinementioning
confidence: 99%
“…The 50 second oscillations and the MAT are part of a process called the defecation motor program (DMP), whereby protons are transported across the basolateral membrane of the intestine by the Na + /H + exchanger PBO-4, where they act as neurotransmitters that trigger muscle contractions required for elimination of waste [16,17]. Using KR35 we previously showed that animals with mutations in pbo-4 fail to produce the MAT during pH oscillations, although other aspects of the acidic wave were grossly normal such as the acidification of the posterior intestine prior to the MAT [18].…”
Section: Pbo-1 Mutants Have An Abrogated Ph Wave In the Intestinementioning
confidence: 99%
“…Our group and others have developed a structurally analogous scaffold, the aminomethylrhodamines or rhodaminedeoxylactams as fluorescent probes for pH, which have a pK a value that is strongly dependent on the electronic properties affecting the amino group [1215]. This approach has allowed us to rationally design rhodamine pH probes where the photophysical response to pH is easily predicted by correlation to the amine's pK a .…”
Section: Introductionmentioning
confidence: 99%